TONSILOLITH: A CASE REPORT - SREEKANTHA; SHEETAL D; SATISHA T G; PRIYA HILDA D’SOUZA; RANGASWAMY R; RAGHAVENDRA TEY; MANJUNATHA GOUD BK; VIVIAN D’SOUZA; PRASANNACHANDRA M (International Journal of Pharma and Bio Sciences, 2011)
Tonsilolith is unusual presentation of stone in tonsillar crypt. Etiology of tonsilolith is multifactorial and not usually diagnosed. Here a patient presented with bad smell from her breath and difficulty in swallowing. Radiological and biochemical investigation helped us to diagnose tonsilolith.